Detection of pathotype of Marek's Disease in layer chicken in Iraq - Anas, Malek (University of Thi-Qar Journal of agricultural research, 2023)
Marek's Disease is a viral disease that affects poultry, particularly chickens. It is caused by the Marek's Disease Virus (MDV), which belongs to the herpesvirus family. The disease is characterized by the formation of tumors in various organs, including the nerves, skin, and internal organs such as the liver, spleen, and kidneys. A layer poultry farm of one day old, vaccinated with Marek's disease virus vaccine. The flock was infected with a virulent Marek's disease virus with a mortality rate of up to 60%. Histopathological examination of affected tissues is an important tool for the diagnosis of the disease. The histopathological finding of tissue sections from chickens with MDV shows extensive proliferation of lymphocytes of various sizes. The confirmation was done by PCR and standardized targeting a 132 bp tandem repeat region specific for serotype-1 MD viruses Meq gene was carried out by PCR and nucleotide sequencing, The sequence analysis of Meq gene of different clinical cases from Iraq homology with very virulent strain and Phylogenetic analysis of oncogenes was carried out with other available sequences in the GenBank we conclude that MDV strains obtained in the present outbreaks in Iraq could be designated as very virulent pathotypes based on nucleotide and phylogenetic analysis of the viruses.